Potencial fisiológico de sementes de soja em resposta aos tratamentos industriais e períodos de armazenamento - Suzukawa, Andréia Kazumi (2014)
Industrial seed treatment is a new reality, ensuring seed coverage and dose with different combinations of agrochemical products; however, there are distinct results from research regarding physiological quality of treated seeds and storage. The hypothesis is that the combination of products affects the physiological potential in each storage period and through the storage periods the effect of the products becomes more accentuated, negatively to the seeds. The aim of the present work was to evaluate physiological potential of soybean seeds in seven treatments associated to six periods of storage (0, 15, 30, 45, 60 and 90 days). The seed treatments were: 1 control (no treatment); 2 combination of fungicide; insecticide and a drying powder; solution volume: 350 mL 100kg-1; 3 fungicide, insecticide, drying powder and addition of micronutrients Cobalt and Molibdenium; solution volume: 550 mL 100kg-1; 4 fungicide, insecticide, drying powder, micronutrients e addition of bioregulator;solution volume: 1050 mL 100kg-1; 5 fungicide, insecticide, drying powder, polymer and an insecticides/acaricides;solution volume: 500 mL 100kg-1; 6 fungicide, insecticide, drying powder, polymer, insecticide/acaricide and micronutrients;solution volume: 700 mL 100kg-1; 7 fungicide, insecticide, drying powder, polymer, insecticide/acaricide, micronutrients and bioregulator; solution volume: 1200 mL 100kg-1.The study was conducted in a completely randomized design in a repeated measures in time scheme. In each period, first and final count of germination test, accelerated aging test, shoot and root length, emergency speed rate in sand and final emergency were carried out. The results make it possible to conclude that treatments 2 (fungicide: thiabendazole, fludioxonil, mefenoxan, insecticide: thiametoxam and drying powder), 3 (fungicide, insecticide, Co and Mo micronutrients and drying powder) and 5 (fungicide, pesticide, insecticide / nematicide, drying powder and polymer) were presented as the best options among the treatments along storage periods. The storage limit period before severe damage occurs to the seeds is 15 days for most treatments. Treatments 4 and 7 were the less promising. The spraying volume of 1050 and 1200 mL for 100 kg-1 of seed and the nature of the products were injurious to seeds. Thus, physiological quality of soybean seeds is affected by different combinations of products and different solution volumes presentingneutral, phytotonics and phytotoxic effects to the seeds, varying upon the combinations of industrial seed treatments and storage periods.